The yurt as a geometric model in teaching mathematics - Tanzy, Mengi V.; Saaya, Syldys K.; Shershneva, Victoria A.; Vainshtein, Yulia V.; Ondar, Choduraa M. (The New Research of Tuva, 2020)
The article deals with the yurt as a model for the study of analytical geometry in the system of education of the Republic of Tuva. The elements of the yurt come as a number of geometrical shapes, such as a cylinder, a truncated cone and part of a sphere (the three main rotation bodies), as well as parallel lines, circles, rectangles, and other figures. Thus the yurt can be seen as the best study model for mastering geometrical knowledge by focusing on the object well-known to students. The authors have developed an electronic training module titled "The yurt as a geometric model in the study of mathematics", working within a virtual learning environment. It includes interactive lectures, simulator tests and individual tasks, and aims to improve command of mathematics and demonstrate the potential of e-learning in practice.